News literacy : uma ferramenta de combate à desordem informacional - Santos, Jéssica de Almeida (2019)
This dissertation investigates the applicability of the discipline of news literacy in middle and high schools in Brazil, considering the focus of the curriculum in training students qualified to deal with news and informational messages, in a context of informational disorder. The study is based on methodological triangulation and is divided into three stages: 1) bibliographic research to understand the complex scenario of informational disorder, impacts on society, journalism and education, and the concepts and relationships between media literacy and news literacy; 2) instrumental case study at the Center for News Literacy, Stony Brook University, USA; with the objective of mapping the contents of the course The Course Pack, and how it dialogues with the demands of the National Curricular Common Base (BNCC) and the learning parameters defined by Potter (2014); and 3) interviews on the applicability of the course in Brazil, considering five main points: relevance of the curriculum to train a critical student in the consumption of news; classroom applicability; evaluation and relationship with other disciplines, teacher training and successful experiences. The research demonstrates that the news literacy curriculum contributes to the formation of a more critical consumer of news, and in Brazil, even with the successful experiences that already exist, there is a great space for dialogue between educators, journalists, government , media groups, and universities so that the school becomes a space for discussion of the theme and provides students with the necessary foundation for them to grow prepared to deal with the avalanche of information of our era.